The proto-germanic n-stems : a study in diachronic morphophonology - Kroonen, Guus, 1979- (Leiden studies in Indo-European ;, 2011)
The n -stems are an intriguing part of Proto-Germanic morphology. Unlike any other noun class, the n -stems have roots that are characterized by systematic consonant and vowel alternations across the different Germanic dialects. This monograph represents a diachronic investigation of this root variation. It traces back the Germanic n -stems to their Indo-European origin, and clarifies their formal characteristics by an interaction of sound law and analogy. This book therefore is not just an attempt to account for the typology of the Germanic n -stems, but also a case study of the impact that s.